Optimasi Formula Sediaan Emulgel Minyak Nimba (Azadirachta indica) menggunakan Response Surface Methodology - Akmal, Tubagus; Yunus, Mohammad (Akademi Farmasi Bumi Siliwangi, 2024)
Neem oil possesses numerous advantages for skin health due to its properties as an antioxidant, antibacterial, antifungal, and wound-healing agent when used topically. Neem oil, due to its numerous advantages for the skin, can be used in cosmetic products, such as emulgel preparations. The objective of this study is to enhance the formulation of neem oil emulgel by adjusting the concentration of olivem 1000 (X1) as an emulsifier and xanthan gum (X2) and guar gum (X3) as gelling agents. Formula optimization was conducted utilizing the Box Behnken Design method in Design Expert v.13.0.1 software. The test responses measured were viscosity (Y1) and pH (Y2). The test yielded 15 test formulations with viscosity and pH values ranging from 12800 ± 505.96 to 66400 ± 438.18 cPs and from 4.67 ± 0.01 to 5.01 ± 0.01, respectively. The study concludes that the optimum formula is achieved by using a concentration of olivem 1000, xanthan gum, and guar gum at 5.00, 0.1, and 0.5, respectively. This formula has a viscosity value of 42600 ± 419.5 cPs and a pH of 4.94 ± 0.1.